Play Therapy using Color Paper to Reduce Mathematic Anxiety on Children’s - Safitri, Prima Nadia; Marjohan, Marjohan; Bentri, Alwen (Journal of ICSAR, 2023)
This study aims to determine the application of Play Therapy using colored paper to reduce mathematical anxiety in children. The research method used is Single Subject Research with an A-B-A design. The subjects of this study were third-grade children of SDN 211 / IX Mendalo Darat. Determination of the subject of this study using purposive sampling technique with the criteria for children's mathematic anxiety conditions are in the very high category. The data collection instrument for this research is the mathematic anxiety scale, interview, and observation. The data analysis technique used is the visual analysis of data and graphics. The findings of this study indicate that Play Therapy using colored paper is effective in reducing children's mathematical anxiety in AA subjects, as the impact of counseling changes in the baseline phase increases during the intervention and stabilizes in the follow-up phase. It is suggested that school counselors apply Play Therapy in developing effective daily life (KES) and eliminating daily effective life (KES-T) which aims to form an independent person.